The archive of faces and the archive of plaster; Reading anthropological facial plaster-casts taken from living individuals from the former Netherlands East Indies - Lai, Laetitia (Wacana, Journal of the Humanities of Indonesia, 2023)
This article introduces two interconnected approaches to provenance research on anthropological facial plaster-casts taken from living individuals. It focuses on three series of facial casts taken by Dutch anthropologist Johannes Pieter Kleiweg de Zwaan (1875-1971) in the Netherlands East Indies in 1907 and 1910. It suggests that “reading” the facial casts as an archive of faces and an archive of plaster has the potential to reveal information systematically left out in their object biographies. Through this reading process, the colonial networks of control and power asymmetries which made the plaster-casting possible are examined. It seeks out additional information to bring the object closer to the person whose face was appropriated for various colonial ends. This epistemological experiment explores the first steps which can be taken to create a decolonial view of the large anthropological plaster-cast collections in European museums which have been left anonymous for decades.